2017
DOI: 10.1038/s41598-017-07736-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carboxylesterase 1 S75N on clopidogrel therapy among acute coronary syndrome patients

Abstract: Carboxylesterase 1 (CES1) hydrolyzes the prodrug clopidogrel to an inactive carboxylic acid metabolite. The effects of CES1 S75N (rs2307240,C>T) on clopidogrel response among 851 acute coronary syndrome patients who came from the north, central and south of China were studied. The occurrence ratios of each endpoint in the CC group were significantly higher than in the CT + TT group for cerebrovascular events (14% vs 4.8%, p < 0.001, OR = 0.31), acute myocardial infarction (15.1% vs 6.1%, p < 0.001, OR = 0.37) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
(25 reference statements)
0
10
0
2
Order By: Relevance
“…The study also found that the S75N polymorphism was more frequent in patients with acute coronary syndrome (MAF 22%) than in the general population (MAF 5%). The authors concluded that there was a significant association between the S75N polymorphism and the outcome of clopidogrel therapy (Xiao et al, 2017). However, this result conflicts with another study that found the S75N variant to be not associated with the outcomes of patients treated with methylphenidate (Johnson et al, 2013).…”
Section: Pharmacogenetics Of Other Ces1 Genetic Variantsmentioning
confidence: 87%
“…The study also found that the S75N polymorphism was more frequent in patients with acute coronary syndrome (MAF 22%) than in the general population (MAF 5%). The authors concluded that there was a significant association between the S75N polymorphism and the outcome of clopidogrel therapy (Xiao et al, 2017). However, this result conflicts with another study that found the S75N variant to be not associated with the outcomes of patients treated with methylphenidate (Johnson et al, 2013).…”
Section: Pharmacogenetics Of Other Ces1 Genetic Variantsmentioning
confidence: 87%
“…Клопидогрел представляет собой тиенопиридин, который превращается в фармакологически активный тиоловый метаболит через неактивный промежуточный 2-оксо-клопидогрел [5]. Реакция катализируется ферментами цитохрома P450, включая CYP2C19, CYP3A, CYP2B6, CYP1A2 и CYP2C9 [7]. Однако только 15% клопидогрела становится биодоступным [7].…”
Section: Discussionunclassified
“…Реакция катализируется ферментами цитохрома P450, включая CYP2C19, CYP3A, CYP2B6, CYP1A2 и CYP2C9 [7]. Однако только 15% клопидогрела становится биодоступным [7]. Активный метаболит 5-тиол клопидогрел ингибирует индуцированную АДФ активацию и агрегацию тромбоцитов путем необратимого связывания с рецептором P2Y 12 на поверхности клеток [8].…”
Section: Discussionunclassified
“…CES1 polymorphism has also been investigated in recent years as a contributing factor to inter‐individual variability of clopidogrel activation and antiplatelet activity. A number of studies documented that the CES1 SNPs G143E (rs71647871) and D260fs16 (rs71647872) exhibited markedly decreased enzymatic activity in the hydrolysis of the CES1 substrates, and CES1A2 −816C as well as CES S75N were associated with attenuated platelet reactivity to clopidogrel . Association of P2Y12 and CES1 polymorphisms to clopidogrel resistance however remains to be verified and warrants further investigation.…”
Section: Cyp Genotype‐based Drug Therapiesmentioning
confidence: 99%